Commentaries on the Dossier “New Participatory and Democratic Institutions in Latin America” - Ortiz Crespo, Santiago (2011)
The author comments on the most relevant ideas appearing in the texts on participatory and democratic institutions, in the 40th issue of Íconos. He then poses a number of questions for an analysis of said institutions at the continental level, in a context in which the notion of citizen participation –emerging from social movements– has been appropriated by current governments in the region. Finally, he centers on the Ecuadorian case, on the basis of which he offers a series of questions and observations that invite the development of further analysis.